Self-reported Sexually Transmitted Infections (STIs) and symptoms among married women in India: Trend, pattern, and influencing factors - Oinam Ashabala Devi; Avijit Mistri (National Geographical Journal of India, 2024)
Around 12 per cent of the married women in India reported an STI or symptoms in 2019-21. All the regions in India have witnessed an increasing trend of STIs- Northern India reported the highest, followed by the Northeast region. The present study examines the trend, pattern and influencing factors for self-reported STIs and symptoms among currently married women in India from 2005-06 to 2019-21 based on NFHS. Women and husbands’ characteristics, and their sexual behaviour are observed in the study as predominant predictors for self-reported STIs and symptoms. The study also reveals that working women are more likely to report STIs/symptoms. Husbands away from home or migration, their multiple sex partners, and paid-for sex are significantly associated with the prevalence of STIs among married women. With the advancement of Indian society, socioeconomic life and sexual behaviour are becoming more complex, which play a crucial role in determining STIs. These need to be considered wisely, along with conventional predictors- age, education, social groups, location of residence, and economic status- to curb the growing STIs in India. Finally, adequate health infrastructure for continuous monitoring of different types of STIs/STDs and a good database are an urgent need for the well management of STIs.